2021
DOI: 10.1371/journal.pone.0256069
|View full text |Cite
|
Sign up to set email alerts
|

Use of latent class analysis as a method of assessing the physical activity level, sedentary behavior and nutritional habit in the adolescents’ lifestyle: A scoping review

Abstract: Background Currently, adolescents’ lifestyle is commonly characterized by physical inactivity, sedentary behavior, and inappropriate eating habits in general. A person-oriented approach as Latent Class Analysis (LCA) can offer more insight than a variable-centered approach when investigating lifestyle practices, habits, and behaviors of adolescent population. Objective The aim of the present study was to assess which variables are mostly used to represent the physical activity level, sedentary behavior SB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 70 publications
7
22
0
Order By: Relevance
“…The results of the present study demonstrated that the males were inclined to enter the “high exercise-high calorie diet” class (class 6) and “moderate exercise-balanced” class (class 2). The previous results reported that the females were more prone to exhibit low exercise and sedentary behavior, as compared to males ( 18 ), which was consistent with the results of this study. The main reason causing females' physical exercise was usually less active than that of males lied in the gender difference of perception barriers, in which, lack of exercise energy and willpower were listed as the main factors ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study demonstrated that the males were inclined to enter the “high exercise-high calorie diet” class (class 6) and “moderate exercise-balanced” class (class 2). The previous results reported that the females were more prone to exhibit low exercise and sedentary behavior, as compared to males ( 18 ), which was consistent with the results of this study. The main reason causing females' physical exercise was usually less active than that of males lied in the gender difference of perception barriers, in which, lack of exercise energy and willpower were listed as the main factors ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Other components of lifestyle, such as sleep habits and health awareness, are also significant variables affecting adolescent obesity, so future research should be analyzed from a multifactorial perspective of adolescent lifestyle behavior. In addition, the vast majority of such surveys were conducted in high-income countries, with a lack of research in middle- and low-income countries ( 18 ). The lifestyle patterns that lead to adolescent obesity are more complex, and are significantly related to factors such as race, culture, and social psychology, and more research support is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tests based on hypotheses are appropriate, procedures obtain the most adjusted, parsimonious, and interpretable model. This is a grouping method appropriate for identifying behavioral patterns [ 50 ] and analysis of iterations and associations between different types of variables related to the most common behaviors adopted by the pediatric population [ 51 ]. LCA was used to model the latent variable "movement behaviors" from five manifest variables related to adolescents PA and sedentary time.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research on families with adolescents has shown that multiple eating behaviours tend to cluster in ways that reflect meaningful heterogeneous eating patterns among individuals that influence their health outcomes 15 . There is some evidence that health-related behaviours patterns comprising diet, physical activity (PA) and/or sedentary behaviour are associated with overweight and obesity among children and adolescents 18 , 19 . However, there is a lack of research that examines how multiple eating behaviours in combination may influence health and HRQoL among children and adolescents.…”
Section: Introductionmentioning
confidence: 99%